FAKTOR-FAKTOR YANG MEMPENGARUHI NILAI PERUSAHAAN DI SEKTOR PROPERTY, REAL ESTATE & BUILDING CONSTRUCTION YANG TERDAFTAR DI BEI PERIODE 2008-2012 - Wahyuni, Tri; Ernawati, Endang; Murhadi, Werner R. (University of Surabaya, 2013)
The aims of this research is to understand the factor affecting the Value of the Firm for Property, Real Estate & Building Construction enterprises enlisted in Indonesian Stock Exchange period 2008-2012. The related theories being used in this research are Dividend Theory, Signaling Theory and Agency Theory. This research uses quantitative perspective with Least Square (LS). Objects used in this research are Property, Real Estate & Building Construction enterprises enlisted in Indonesian Stock Exchange period 2008-2012. About 110 object are investigated (17 Property & Real Estate and 5 Building Construction). After conducting this research, the author found that Investment Decision (PER), Size and Profitability has significant positive effect to the Value of the Firm. Financing Decision (DER) variable has significant negative effect to the Value of the Firm. Furthermore, Dividend Policy has insignificant positive effect to the Value of the Firm. Institution Ownership has insignificant negative effect to the Value of the Firm.